Storying sports injury experiences of elite track athletes: A narrative analysis. (September 2021) - Everard, Ciara; Wadey, Ross; Howells, Karen
Abstract: Objective: Taking a social and cultural perspective, this study extends research in the field of sport injury psychology by storying elite track athletes injury experiences to identify dominant socio-cultural narratives that structure their tales. Methods: Fifteen elite track athletes participated. Data collection spanned 18 months and involved two methods of collection: life-story interviews and timelining. A total of 42 interviews were collected. Dialogical narrative analysis was used to identify the narrative typologies. Results: Six narrative typologies were identified: Resilience, Merry-Go-Round, Longevity, Pendulum, Snowball, and MoretoMe. Conclusion: This study extends the sport injury psychology evidence-base by highlighting how socio-cultural practices and processes influenced the thoughts, feelings, and behaviours of athletes throughout the full spectrum of injury. By creating and sharing narratives of injury, we can expand the opportunities available to athletes to enable them to make sense of their injury experiences in diverse and meaningful ways. Highlights: Athletes' psychological experiences of injury are shaped by socio-cultural injury narratives. Six injury narrative typologies were uncovered. These were Resilience, Merry-Go-Round, Longevity, Pendulum, Snowball and More to Me . Sharing narratives expands athletes' opportunities to make sense of their injury experiences.